Course "introduction to profession" as a part of CDIO approach implementation - Pavlovskaya, Irina (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
This article considers the importance of creating motivation to study for students through deep diving into atmosphere of future profession. Course "Introduction to profession" suggested as a tool to solve this by the example of quality management. The course is fully complined with CDIO Initiative approach.